África e população negra nos livros de História no Brasil: um estudo de obras didáticas para o Ensino Fundamental II - Pereira, Pedro Sérgio (2019)
The present dissertation has thematic area to Africa and the black population in the books of History in Brazil. The general objective is to investigate the influence of Law 10.639 / 03 on the production of History textbooks aimed at the student audience that attends the Elementary School segment in Brazil. Law 10.639 / 03 established the obligation to teach the History of Africa and Afro-descendant populations in Brazilian schools and this led to changes in the textbooks of History. In order to develop the research, a documentary study was carried out comparing two didactic collections published by the same author and the same publisher: a collection from the year 1995, before to the promulgation of the Law, and another collection from 2016, when the Law was in force there were 13 years. It was based on the hypothesis that there was in the history books a naturalization of the absence of the Negro and an emphasis on Eurocentrism before the law was enacted, and these elements were taken as components of what was supposed to be part of the subjective dimension of the teaching of History. It was concluded that due to Law 10.639 / 03 there was an inflection in the production of didactic materials in the History area with a greater presence of positive references to Africa, to the Brazilian black population and also to movements carried out by blacks in America